Case report: NAFLD and maple syrup urine disease: Is there an interplay between branched-chain amino acids and fructose consumption? - Moreira-Silva, Helena; Ferreira, Sandra; Almeida, Manuela; Gonçalves, Isabel; Cipriano, Maria Augusta; Vizcaíno, J. R.; Santos-Silva, Ermelinda; Gomes-Martins, Esmeralda (Frontiers in Pediatrics, 2022)
Background The worldwide increase in pediatric overweight and obesity, in parallel with the global increase in the consumption of sucrose and fructose, is associated with non-alcoholic fatty liver disease (NAFLD). Elevated branched-chain amino acids (BCAAs) are a metabolic feature related to obesity and an early risk factor for insulin resistance and NAFLD. However, few studies have assessed metabolic risk factors and nutritional status in maple syrup urine disease (MSUD) patients under restricted BCAA and high carbohydrate diets. Methods and results Herein, we present a pilot report of a 17-year-old boy with classic MSUD with poor diet compliance and high fructose consumption, mainly during early adolescence. At that time, he was overweight and developed features of metabolic syndrome, including persistently elevated liver enzymes and hepatic steatosis. He underwent liver transplantation at the age of 13 years to prevent the risk of progressive cognitive impairment. Two months later, NAFLD relapsed in the graft, despite a better BCAA balance and weight loss. Nevertheless, 6 months after dietary restriction of fructose consumption, NAFLD had sustainably improved. Conclusion Childhood overweight and fructose overconsumption are wellestablished driving forces in the development of pediatric NAFLD. However, their role in the early onset and progression of NAFLD in the allograft remains to be established. Furthermore, it is not known whether the dysmetabolic state associated with elevated BCAAs may be contributory. Further studies are required with a cohort of MSUD subjects to validate our findings and to ascertain the possible interaction between a BCAA imbalance and dietary intake in the development of NAFLD.